2013
DOI: 10.3109/01612840.2012.753560
|View full text |Cite
|
Sign up to set email alerts
|

Active Coping, Personal Satisfaction, and Attachment to Land in Older African-American Farmers

Abstract: Elevated suicide mortality rates have been reported for farmers and for the elderly. Very little literature exists that looks at the health of older minority farmers. This mixed-method study describes older African-American farmers (N = 156) in the contexts of active coping, personal satisfaction from farm work, and attachment to their farmland to provide insight into the psychosocial dimensions of their mental health. Findings show that the farmers have positive perspectives on work and farm future, and stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
11
0
3
Order By: Relevance
“…15 Another benefit of farming is the person's attachment to the land, as reported by older African American farmers. 16 More specifically, many older adults feel responsibility for the land that has been passed down by their family, and working on that land helps align with many older adults' definition of healthnamely, as the ability to work. 17 These background factors might have interacted to prevent new LTCI certification and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Another benefit of farming is the person's attachment to the land, as reported by older African American farmers. 16 More specifically, many older adults feel responsibility for the land that has been passed down by their family, and working on that land helps align with many older adults' definition of healthnamely, as the ability to work. 17 These background factors might have interacted to prevent new LTCI certification and death.…”
Section: Discussionmentioning
confidence: 99%
“…Both frailty and vitamin D deficiency have been separately associated with an increased risk of adverse health outcomes and mortality . Another benefit of farming is the person’s attachment to the land, as reported by older African American farmers . More specifically, many older adults feel responsibility for the land that has been passed down by their family, and working on that land helps align with many older adults’ definition of health – namely, as the ability to work .…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on sustained work indicators of older farmers suggested that perhaps the most important intervention is to acknowledge the importance of work to older farmers (Maciuba et al, 2013;Reed et al, 2012). Farm work provides a sense of accomplishment, satisfaction, and enjoyment that is therapeutic to farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Farm work provides enjoyment and satisfaction, and cannot be disconnected from senior farmers' heritage and culture. Older farmers firmly link life satisfaction to their sense of accomplishment from their work (Maciuba et al, 2013;Reed et al, 2012), and they define good health as the ability to work (Reed et al, 2012). The desire and need to work align closely with the continuity theory of aging, which proposes that individuals age successfully when they continue their habits, preferences, lifestyles, and relationships from midlife into late life (Gullifer and Thompson, 2006).…”
mentioning
confidence: 80%
“…Maciuba, Westneat, & Reed (2013) discuss the intertwined nature of the occupation of farming and the lives of the farmers, further highlighting the importance of good health both mentally and physically. Mental health in the farming community remains underdeveloped.Financial stressors have been linked with increased suicide rates and suicidal ideations among farmers(Maciuba, Westneat, & Reed, 2013). Suicide is one of many mental health conditions that are routinely seen in the farming community, along with depression, and overall poor health status(Maciuba, Westneat, & Reed, 2013).…”
mentioning
confidence: 99%